John Owen, Richard Baxter and the Formation of Nonconformity - Cooper, Tim (Taylor & Francis Ltd, 2024)
John Owen (1616-1683) and Richard Baxter (1615-1691) were both pivotal figures in forming the nonconformist landscape of Restoration England. Yet despite having much in common, they found themselves taking opposite sides in the theological debates that swept through Protestantism in the second half of the seventeenth century. By comparing and contr